Principles Of Poetry in Utopia in Umayyad and Abbasid ‘S Era: Love and Happiness as An Example (Raparin Journal of Humanities (RJH), 2025)
This research attempts to portray the principles of (happiness and love) for Utopia in Umayyad and Abbasid’s poetry because human virtues since the beginning of history have been cared for by scholars and intellectuals, especially poets. Those social issues appear and the world depends on them in explaining its internal and external factors, which determining the nature of things and setting determinants for them, and among them are those matters that maintains a source of nerves and disorder for people in various times and places, the issue of love that people gain and achieve in the world that around them; For a peaceful and doubtful life, and a life filled with happiness and friendliness. We will attempt to discover the principles of love and happiness for utopia in the time of Umayyad and Abbasid poetry to build the world in which poet lives, and the main source of this love and happiness quite different according to his views for them. Those poets of the Umayyad and Abbasid time assume that presented them by shaping this principle according to his personal perspectives and his own view of it, so each of them showed it.According to what he saw in his various poetic goals, as much as the social and linguistic culture exist to him, the impact of which was appeared in his ability to show this unique world of which he could to be one of its members in various forms. The out comes in the introduction, preface, and two sections, with requested under them, and to achieve the goals. In the mentioned research, we depend on the historical method, and descriptive method. Eventually, presenting the most important results recorded by the research with a list of sources and references.